INTERPRETATION AND IMPLICATION OF DEFAULT BY THE CONSTITUTIONAL COURT RELATED TO THE EXECUTION OF FIDUCIARY - Agung Pitra Maulana (Surakarta Law and Society Journal, 2020)
The purpose of this research is to find out how the interpretation of promise injury related to the execution of the object of Fiduciary in the Constitutional Court Decision No. 18 / PUU-XVII / 2019 and to find out what are the implications of the Constitutional Court Decision. The research method in this research is normative legal research. Normative legal research is a process to find legal rules, legal principles, and legal doctrines in order to address legal issues. The result of this research is application for testing Article 15 paragraph (2) and paragraph (3) of Law No. 42/1999 has been decided by Constitutional Court on January 6, 2020. The purpose of this study is to find out how the interpretation of Constitutional Court on meaning of "default" related to fiducia security execution and what implications are. This research used normative legal research method. The results showed that Constitutional Court interpreted: first, the existence of "default" was not determined unilaterally by creditor, but on the basis of an agreement between creditor and debtor. Second, for fiduciary security objects for which there is no agreement "default", then all legal mechanisms in execution apply as same as implementation of a court decision with permanent legal force. The implication: first, the meaning of "default" must be agreed by both parties. Second, if debtor refuses execution, then creditor must file a lawsuit in court. Third, the potential for widespread testing of Mortgage Law. Fourth, the court will be far more active and creditor will incur more expensive fees. Fifth, there will be potential debtor who deliberately gain time through a lawsuit in court. In addition to juridical implications, this can also have implications for economic sector. Keywords: Constitutional Court, default, fiduciary